The ultrafast phase-change memory with high-thermal stability based on SiC-doped antimony. (1st March 2017) - Guo, Tianqi; Song, Sannian; Li, Le; Ji, Xinglong; Li, Chang; Xu, Chang; Shen, Lanlan; Xue, Yuan; Liu, Bo; Song, Zhitang; Qi, Ming; Feng, Songlin
Abstract: The contradictory between switching speed and thermal stability has long been a huge challenge for phase-change memory applications. For providing a feasible solution, the rapid-phase-transition material — pure antimony, was incorporated with silicon carbide to complement their advantages. The characterization results elucidate that dopants situated in the grain boundary inhibit the crystal growth and enhance the stability of the temperature-sensitive amorphous state. Convincingly for devices, an ultrafast speed of 7 ns, an operational voltage requirement of only 1.0 V, a high endurance of more than 200 K and a long data retention are all demonstrated to be realizable and repeatable. Graphical abstract: SiC doping Sb is a feasible solution to overcome the contradictory nature of traditional phase-change materials. That both fast speed and high stability can be achieved at the same time is of great importance. And the experimental data have put in evidence that adding SiC impurities to pure Sb raises the crystallization temperature ( T c 236 °C) and the corresponding activation energy ( E a 2.8 eV) for (SiC)4.5 Sb91 . Thus it further leads to the favorable data retention ( T 10 - yr 119 °C), especially maintains the ultrafast switching speed (7 ns) and holds a set of low operation voltages (1.0 V) in (SiC)4.5 Sb91 -based devices.